Análise da relação entre cognição e estabilidade da marcha em idosos - Mello, Natalia Ferraz (2018)
The present study is structured as follows: a brief introduction and the methodological aspects of the research and two original research articles. The aim of the present study was to gather information about the physiological changes that occurred in the aging process and its consequences on cognition and stability during the elderly, exploring the perceptual motor variables related to Postural Control (CP). Subsequently, the methodology of the study with general aspects of the dissertation is presented. Article I, titled "Evaluation of gait in the elderly during double task, had as objective to analyze the effect of the Double Task on the Postural Control during walking. Article II, entitled "Relation of the dual task with the perceptive-motor variables in the Elderly", aimed to verify the correlation of the double task (DT) with the perceptive motor variables. Finally, this paper concludes with the combined results of the two articles, as well as research perspectives for future studies aiming to analyze the stability of walking in different populations.